1986
DOI: 10.1017/s0031182000064192
|View full text |Cite
|
Sign up to set email alerts
|

Environmental sex determination and density-dependent population regulation in the entomogenous nematodeRomanomermis culicivorax

Abstract: SUMMARYEnvironmental sex determination in the mermithid nematodeRomanomermisculicivorax is examined in the context of parasite reproductive success and population regulation. Experimental results show that the sex ratio of the nematode within its mosquito host (Culex quinquefasciatus) is dependent on parasite density. Sex ratios are biased to females at low parasite burdens and to males at high parasite burdens. Low temperature further enhances female-biased ratios. The net effect of density-dependent sex dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 31 publications
2
34
0
1
Order By: Relevance
“…Morph development in the parasitic nematode Strongyloides ratti is controlled by two developmental switches: host immune status and environmental temperature (Harvey et al 2000). In Romanomermis culicivorax, sex is cued by temperature and parasite density within the host (Tingley and Anderson 1986). To our knowledge, the only other record of a dual cue for ESD comes from the fish Poecilia sphenops, in which sex determination is cued by the interaction between temperature and salinity (Baron et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Morph development in the parasitic nematode Strongyloides ratti is controlled by two developmental switches: host immune status and environmental temperature (Harvey et al 2000). In Romanomermis culicivorax, sex is cued by temperature and parasite density within the host (Tingley and Anderson 1986). To our knowledge, the only other record of a dual cue for ESD comes from the fish Poecilia sphenops, in which sex determination is cued by the interaction between temperature and salinity (Baron et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This type of scramble competition in insect parasitoids was regarded by Taylor (1988) as having an unstable trajectory due to excessive competition. Tingley and Anderson (1986), however, suggest that mermithid nematodes may not closely follow this pattern because of their longer life cycle relative to the host. In a 3-yr field study, Micieli et al (2012) observed that the frequency over time and the level of infection by S. spiculatus were key parameters in regulating populations of Ochlerotatus albifasciatus.…”
Section: Fig 1 Time Required By Individual Romanomermis Iyengari Andmentioning
confidence: 99%
“…When mosquito population density is low, the outcome may be more frequent superparasitism and a skewed mermithid sex ratio favoring males. Superparasitism provides mermithid population reduction, regulation, and stability by relaxing pressure on the host population (Tingley and Anderson, 1986;Sanad et al, 2013). Conversely, when mosquitoes are abundant, the already reduced mermithid population encounters less competition, less superparasitism, more nutrients and consequently produce more females to boost their population to track an expanding host population.…”
Section: Fig 1 Time Required By Individual Romanomermis Iyengari Andmentioning
confidence: 99%
See 2 more Smart Citations